Drama and performance in Hellenistic poetry - Harder, Annette; Regtuit, R. F. (Remco F.); Wakker, G. C. (Hellenistica Groningana, 2018)
This volume is devoted to aspects of performance in Hellenistic poetry. This theme is approached from various angles. Although drama has long been regarded as typical of fifth century Athens, there is an increasing awareness among classical scholars of the importance of drama also for the Hellenistic period. In that period too drama was still written and performed, but at the same time it also was an important object of study and a source of inspiration for works in other genres, such as the epic of Apollonius Rhodius, for new literary forms like the idylls of Theocritus or the mimiambs of Herodas, or for literary experiments such as the extended messenger speech in the Alexandra of Lycophron. Besides, performance was never restricted to drama, but from the archaic period onwards was essential to the presentation of poetry to an audience and thus remained an integral part of Greek cultural life in all periods, also in times of increasing literacy like the Hellenistic period. Therefore in this volume also epic and didactic poetry as well as shorter works from, e.g., a cultic, ritual or sympotic sphere have been studied from the point of view of performance. The various articles show that the focus on performance is a fruitful perspective for looking at Hellenistic poetry.